2007
DOI: 10.12968/gasn.2007.5.3.23472
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of parastomal hernia: a comparison of results 3 years on

Abstract: Parastomal hernia continues to be a common and distressing problem for patients with stomas and research investigating prevention strategies is scant. In March 2005 Thompson and Trainor reported that the introduction of a prevention programme for 1 year following stoma formation surgery significantly reduced the incidence of parastomal hernia. This follow-up study strengthens the reliability and validity of the findings of the first study by confirming a statistically significant reduction in the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Peristomal mesh [38], surgical techniques [39][40][41] and non-surgical options, e.g. abdominal exercise, may warrant further attention [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Peristomal mesh [38], surgical techniques [39][40][41] and non-surgical options, e.g. abdominal exercise, may warrant further attention [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In concluding their review, Bland and Young (2016) recommended a non-invasive preventive approach to managing parastomal hernia. Previous studies have explored such programmes (Thompson and Trainer, 2005;Thompson and Trainor, 2007;Kald et al, 2008;Thompson, 2010). However, a more recent study reported a significant reduction in the incidence of parastomal hernia following a programme that offered participants advice solely on lifting, abdominal exercises and wearing a support garment (North, 2014).…”
Section: Preventionmentioning
confidence: 99%
“…There is research to suggest that use of an abdominal support and undertaking abdominal exercises will assist in the prevention of a parastomal hernia. 45,46 Krouse et al identified that intimacy was the most affected issue for both men and women. 34 Wu et al also reported that about 30% of ostomates lacked confidence in relation to sexual activities but also, that many did not respond to this topic in the questionnaire.…”
Section: Resuming Activities After Stoma Forming Surgerymentioning
confidence: 99%